An examination of aspartate decarboxylase and glutamate decarboxylase activity in mosquitoes - Richardson, Graham (2009)
A major pathway of beta-alanine synthesis in insects is through the alpha-decarboxylation of aspartate, but the enzyme involved in the decarboxylation of aspartate has not been clearly defined in mosquitoes and characterized in any insect species. In this study, we expressed two putative mosquito glutamate decarboxylase-like enzymes of mosquitoes and critically analyzed their substrate specificity and biochemical properties. Our results provide clear biochemical evidence establishing that one of them is an aspartate decarboxylase and the other is a glutamate decarboxylase. The mosquito aspartate decarboxylase functions exclusively on the production of beta-alanine with no activity with glutamate. Likewise the mosquito glutamate decarboxylase is highly specific to glutamate with essentially no activity with aspartate. Although insect aspartate decarboxylase shares high sequence identity with glutamate decarboxylase, we are able to closely predict aspartate decarboxylase from glutamate decarboxylase based on the difference of their active site residues.